Antiplasmodial activity of four Kenyan medicinal plants - Omulokoli, E.; Khan, B.; Chhabra, S.C.
A preliminary antiplasmodial and phytochemical screening of four Kenyan medicinal plants was carried out. The medicinal plants were extracted and tested for in vitro antiplasmodial activity against chloroquine-sensitive (K67)and chloroquine-resistant (ENT36)strains of Plasmodium falciparum. Out of 16 extracts, 12 were active against ENT36 strain while seven were active against K67 strain, that is, IC50 = 50 g/ml. The most active extracts on both strains were those of leaves of Phyllanthus reticulatus Poir. and Suregada zanzibariensis Baill. (Euphorbiaceae)with IC50 = 10 g/ml. The stembark of Terminalia spinosa Engl. (Combretaceae)and the stems of Dissotis brazzae Cogn. (Melastomataceae)had IC50 = 10 g/ml for strains K67 and ENT36, respectively. A preliminary phytochemical analysis of these plants revealed the presence of different classes of primary and secondary metabolites.
Keywords: PLANT EXTRACTS; ANTIPLASMODIAL; PHYTOCHEMISTRY; PLASMODIUM FALCIPARUM; PHYLLANTHUS RETICULATUS; SUREGADA ZANZIBARIENSIS; TERMINALIA SPINOSA; DISSOTIS BRAZZAE